Spontaneous coronary artery dissection in the third trimester—Implications for investigation and delivery. Issue 8 (21st August 2021) - Paxton‐Hall, Thomas; Desai, Pranali; Seton, Nicholas; Arthur, Chris
Abstract: This case of spontaneous coronary artery dissection in pregnancy highlights the diagnostic, treatment and delivery dilemmas in the antepartum period. This is a rare condition that usually manifests in the postpartum period. This case provides multidisciplinary considerations that were encountered for optimal maternal and fetal outcome. Abstract : This case of spontaneous coronary artery dissection in pregnancy highlights the diagnostic, treatment and delivery dilemmas in the antepartum period. This is a rare condition that usually manifests in the postpartum period. This case provides multidisciplinary considerations that were encountered for optimal maternal and fetal outcome.